Do Sovereign Bonds Benefit Corporate Bonds in Emerging Markets? - Dittmar, Robert F.; Yuan, Kathy (Review of Financial Studies, 2008)
We analyze the impact of emerging-market sovereign bonds on emerging-market corporate bonds by examining their spanning enhancement, price discovery, and issuance effects. We find that the effect of spanning enhancement is positive and large; over one-fifth of the information in corporate yield spreads is traced to innovations in sovereign bonds; and most of these effects are due to discovery and spanning of systematic risks. Further, issuance of sovereign bonds, controlling for endogeneity of market-timing decisions, lowers corporate yield and bid-ask spreads. Our results indicate that sovereign securities act as benchmarks and suggest they promote a vibrant corporate bond market.